International courts in Latin America and the Caribbean : foundations and authority - Caserta, Salvatore (Oxford : Oxford University Press, 2021)
This work explores the foundations and evolution of the four Latin American and Caribbean regional economic courts. It argues that local socio-political factors are often the decisive factor in influencing the direction of these Courts, rather than the formally delegated functions they were assigned when established.
This edition previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 17, 2021).
Keywords: Corte de Justicia Centroamericana; Caribbean Court of Justice; Tribunal de Justicia de la Comunidad Andina; MERCOSUR (Organization). -- Tribunal Permanente de Revisiâon.; International courts -- Latin America; International courts -- Caribbean Area; Commercial courts -- Latin America; Commercial courts -- Caribbean Area